The Effect of Korean Wave on K-Beauty Exports in Indonesia: Focus of Gen Z Study as Target Market - Harahap, Wardah Qoniah; Yumitro, Gonda (Jurusan Ilmu Hubungan Internasional, 2025)
The Korean Wave, which encompasses Korean music, drama and lifestyle, has had a significant impact on global consumer preferences, including in Indonesia. This research aims to analyze the influence of the Korean Wave on the export of K-Beauty products to Indonesia, with a focus on Generation Z as the main market. This research uses a descriptive qualitative approach with data collection through systematic literature study and secondary data analysis from KOTRA, Korea Customs Service, as well as semi-structured interviews with 15 Gen Z informants. Results show that exposure to Korean culture significantly increases attraction. The results show that the intensity of exposure to Korean culture affects Gen Z's perceived value, lifestyle identity and brand loyalty towards K-Beauty products. The findings have strategic implications for industry players and policy makers in designing more relevant cross-cultural marketing strategies, as well as opening up opportunities for the expansion of the K-Beauty export market in Southeast Asia through a popular culture-based approach. n and consumption of K-Beauty products. The findings have important implications for South Korea's cross-cultural marketing and export expansion strategies.